Prevalence, Characterization And Biofilm Formation Of Toxigenic Bacillus Cereus Isolated From Ready-To-Eat Cooked Rice In Penang - Navaneethan, Yugenraj (2020)
Bacillus cereus is an important foodborne pathogen causing intoxication and toxico-infection in human. B. cereus can persist in food and environment due to its ability to produce spore and grow in biofilm, resulting in its presence even in processed food such as cooked rice. Mishandling of foods especially in time-temperature abused condition creates favourable conditions for the growth of B. cereus which subsequently produce emetic toxin and enterotoxins. B. cereus also plays significant roles in dissemination of resistant genes and emergence of antibiotic resistant strains. Moreover, B. cereus can cause food spoilage through its enzymatic activities. Hence, this study was undertaken to determine the prevalence of B. cereus in 100 cooked rice samples randomly collected from food outlets in Penang Island. Moreover, the studies on the different B. cereus strains’ characteristics that are relevant in food poisoning, food spoilage, antibiotic resistance and potentiality to promote recurrent contamination were also carried out.